1985
DOI: 10.1128/iai.48.2.384-388.1985
|View full text |Cite
|
Sign up to set email alerts
|

Use of auxotyping for epidemiological studies of Campylobacter jejuni and Campylobacter coli infections

Abstract: A chemically defined medium developed for Neisseria gonorrhoeae was modified to support the growth of Campylobacterjejuni and Campylobacter coli. A total of 76 isolates of C. jejuni and 14 isolates of C. coli were tested on this medium, which was designated Campylobacter defined medium (CDM), over a 3-month period. Although none of the C. coli isolates appeared to require amino acids, 51% of the C. jejuni tested required one and 7% required multiple amino acids for growth. An analysis of isolates obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…The headspace of these bottles was flushed with a gas mixture as mentioned above (overpressure of 500 hPa). The bottles were incubated stationary for 1 week in water baths at 4,10,20,28,30,31,33,35,37,39,42,44, and 46°C. Samples for plate counts were taken at regular time intervals by piercing the rubber stoppers with a syringe.…”
Section: Methodsmentioning
confidence: 99%
“…The headspace of these bottles was flushed with a gas mixture as mentioned above (overpressure of 500 hPa). The bottles were incubated stationary for 1 week in water baths at 4,10,20,28,30,31,33,35,37,39,42,44, and 46°C. Samples for plate counts were taken at regular time intervals by piercing the rubber stoppers with a syringe.…”
Section: Methodsmentioning
confidence: 99%
“…The agar-solidified defined media described by Tenover et al (1985) and by Dickgiesser and Czylwik (1985) for auxotyping Camp. jejuni and Camp.…”
Section: Culture Mediamentioning
confidence: 99%
“…jejuni and Camp. coli (Tenover et al 1985;Dickgiesser and Czylwik 198.5) but these media have not been used for estimating oxygen tolerance by comparing the number of colonies which develop at various oxygen concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter jejuni is generally regarded as requiring oxygen concentrations of 3-15% and carbon dioxide concentrations of 3-5% to grow (Smibert 1986). It can also grow anaerobically in a defined medium (Tenover et al 1985) and some strains have been found to grow slightly under aerobic conditions (Smibert 1986). However, in a more recent report, all Camp.…”
Section: Introductionmentioning
confidence: 99%